D60. Health Effects of Smoking 2012
DOI: 10.1164/ajrccm-conference.2012.185.1_meetingabstracts.a6054
|View full text |Cite
|
Sign up to set email alerts
|

Acute Cigarette Smoke Exposure Induces Cytotoxicity And Inflammation In Living Tissue Of Precision-Cut Lung Slices

Abstract: Chronic obstructive pulmonary disease (COPD) is a severe lung disease with high mortality and increasing prevalence. It is characterized by profound damage of lung parenchyma due to cigarette smoke-induced stress. Lipopolysaccharide (LPS) is a widely used model compound which does not directly induce oxidative stress due to lacking radicals. It therefore can not reflect cigarette smokeinduced toxicity in the lung. The aim of this study is to establish precision-cut lung slices (PCLS) as a relevant toxicity mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Comparison of the airway responses across ex vivo and in vivo exposure models suggests similar trends: diesel engine exhaust was found to induce increased protein expression of the pro-inflammatory marker TNFα in both PCLS prepared from rat lung tissue exposed at an air-liquid interface and in lavage samples collected from rat lungs following inhalation exposure (Morin et al, 2008). Studies have reported increased protein expression of TNFα in response to particulate pollutants, such as engineered silica nanoparticles (Neuhaus et al, 2013), cigarette smoke (Lauenstein et al, 2012) and diesel engine exhaust particulate matter (Bion et al, 2002).…”
Section: Introductionmentioning
confidence: 79%
“…Comparison of the airway responses across ex vivo and in vivo exposure models suggests similar trends: diesel engine exhaust was found to induce increased protein expression of the pro-inflammatory marker TNFα in both PCLS prepared from rat lung tissue exposed at an air-liquid interface and in lavage samples collected from rat lungs following inhalation exposure (Morin et al, 2008). Studies have reported increased protein expression of TNFα in response to particulate pollutants, such as engineered silica nanoparticles (Neuhaus et al, 2013), cigarette smoke (Lauenstein et al, 2012) and diesel engine exhaust particulate matter (Bion et al, 2002).…”
Section: Introductionmentioning
confidence: 79%